2000
DOI: 10.1029/1999jd901165
|View full text |Cite
|
Sign up to set email alerts
|

Columnar physical and radiative properties of atmospheric aerosols in north central Spain

Abstract: Abstract. Direct solar irradiance spectra under clear skies have been measured in a rural station in the region of Castilla y Le6n in north central Spain from March to November 1995 to determine the physical and radiative characteristics of atmospheric aerosols. About 300 spectrawere measured with a LI-COR Model LI-1800 spectroradiometer, with a spectral resolution (full width at half maximum) of 6 nm from 300 nm to 1100 nm. This moderately high spectral resolution permitted the retrieval of the spectral aeros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 55 publications
2
31
1
1
Order By: Relevance
“…5, shows large portion of particles between the 0 < τ a500 < 1.0 and α > 1.5 or a clear fine mode regime. The α is commonly used as an indicator of the predominant aerosol size and eventually the source, because the spectral shape of the extinction is related to the particle size (Eck et al, 1999;Cachorro et al, 2000b;Schuster et al, 2006). The second largest concentration of particles can be found between AOD levels of the order of 1.0 < τ a500 < 4.0 with associated α > 1.0.…”
Section: Resultsmentioning
confidence: 99%
“…5, shows large portion of particles between the 0 < τ a500 < 1.0 and α > 1.5 or a clear fine mode regime. The α is commonly used as an indicator of the predominant aerosol size and eventually the source, because the spectral shape of the extinction is related to the particle size (Eck et al, 1999;Cachorro et al, 2000b;Schuster et al, 2006). The second largest concentration of particles can be found between AOD levels of the order of 1.0 < τ a500 < 4.0 with associated α > 1.0.…”
Section: Resultsmentioning
confidence: 99%
“…This aerosol density value has been used in previous studies of continental regions in the Iberian Peninsula (Cachorro et al 2000), and can be justi ed as a result of the rather dry conditions characteristic of the area. By de nition m L depends on the total columnar number of particles, but it also displays a clear dependence on larger sized aerosols.…”
Section: Aerosol Size Distribution (A) Methodologymentioning
confidence: 99%
“…In spite of the poor correlation between the AOD and α parameter [5,7] values, both quantities must be considered for a realistic analysis. The studies by [3] showed that α value depends strongly on the spectral range.…”
Section: Variation Of Angstrom Parameters α and βmentioning
confidence: 99%